The effect of temperature increase on the development of Rhodnius prolixus and the course of Trypanosoma cruzi metacyclogenesis (2018)
The increase in the global land temperature, expected under predictions of climate change, can directly affect the transmission of some infectious diseases, including Chagas disease, an anthropozoonosis caused by Trypanosoma cruzi and transmitted by arthropod vectors of the subfamily Triatominae. This work seeks to study the effects of temperature on the development of the life cycle, fertility and fecundity of the insect vector Rhodnius prolixus and on the metacyclogenesis of T. cruzi. All of the variables were subjected to 3 temperatures: 26°C, 28°C and 30°C. Hatching time was evaluated, along with time to fifth instar, time to adult, fecundity studied using the e-value, and egg viability during the first 3 reproductive cycles. In addition, the amounts of metacyclic trypomastigotes of the TcI and TcII DTUs in R. prolixus were evaluated from days 2 to 20 at two-day intervals and from weeks 6 to 8 post-infection. Decreases were observed in time to hatching (15–10 days on average) and in time to fifth instar (70–60 days on average) and transition to adult (100–85 days on average). No significant differences in egg viability were observed in any of the reproductive cycles evaluated, but an increase in fecundity was observed at 30°C during the third reproductive cycle. At 30°C, there was also an increase in the number of infective forms and a decrease in the time at which metacyclic trypomastigotes were detected in the rectal ampulla of the insects for both TcI and TcII. According to these results, the expected temperature increase under climate change would cause an increase in the number of insects and a greater probability of infection of the parasite, which affects the transmission of Chagas disease. © 2018 Tamayo et al. http://creativecommons.org/licenses/by/4.0/.